Optimizing The Use Of Artificial Intelligence In English Language Learning: A Literature Review - Arbi, Anggun Purnomo (PT. Gudang Pustaka Cendekia, 2024)
This research aims to explore and analyze applications of artificial intelligence (AI) in English language learning, focusing on tools such as ChatGPT, ELSA Speak, and Perplexity. The literature review involved a library research method to synthesize findings from various sources. The results identified a significant range of AI applications in English language learning, including conversational interaction, presentation creation, illustration tutoring, individualized tutoring, material creation, illustration creation, and voice generation technologies. The findings underscore the potential of AI to improve the interactivity, personalization, and efficiency of English language learning. Suggestions for future research include continued research on long-term efficacy, ethical considerations, equitable access, integration with traditional methods, and user experience. This research is vital in bringing an in-depth understanding of the transformation of language learning through the utilization of AI technology.